Comparative Analysis of Broiler Chicken Productivity in Relation to the El Niño and La Niña - Yusuf, Muhammad; Asri, Haryanto (Hasanuddin Journal of Animal Science (HAJAS), 2024)
This study aims to analyze the impact of El Niño and La Niña on the productivity of broiler chickens in Mamuju Regency, West Sulawesi. The research was conducted in June 2024 using data from broiler farms that implement a close-house system. The research method involved collecting broiler productivity data, including feed consumption, weight gain (WG), Feed Conversion Ratio (FCR), mortality, and Performance Index (PI), as well as climate data such as temperature, rainfall, and humidity.The results showed significant differences in broiler productivity between the El Niño and La Niña periods. During La Niña, feed consumption (0.098 kg/bird/day) and WG (0.063 kg/bird/day) were higher compared to the El Niño period (0.088 kg/bird/day and 0.057 kg/bird/day). FCR remained stable (1.5) in both conditions, indicating consistent feed conversion efficiency. Mortality was slightly higher during La Niña (5.11%) than El Niño (4.80%). The Performance Index (PI) was higher during La Niña (393) than El Niño (360), indicating better overall productivity.  Multiple linear regression analysis showed that climate variables (La Niña intensity, temperature, rainfall, and humidity) did not significantly affect the PI. A SWOT analysis identified an offensive strategy as the optimal approach, leveraging the strengths of the closed house system and the growing market opportunities. The conclusion of this study indicates that although there are productivity differences between El Niño and La Niña periods, the use of closed-house technology helps maintain production stability. This research highlights the importance of technological adaptation in addressing climate variability to sustain broiler farm productivity. Keywords: El Nino, La Nina, broiler productivity, close house, climate variability